PENGARUH RETURN ON ASSETS, DEBT TO EQUITY RATIO DAN PRICE TO BOOK VALUE TERHADAP RETURN SAHAM PERUSAHAAN LQ45 TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2016 – 2018 - Eka Putra Jaya; Randy Kuswanto (Jurnal Bina Akuntansi, 2021)
This research was conducted to examine the effect of Return on Assets, Debt to Equity Ratio and Price to Book Value on LQ45 Company's stock returns listed on the Indonesia Stock Exchange in the period of 2016 - 2018. Data collection techniques used were documentation using secondary data. The data analysis method used is a quantitative method with associative and descriptive method approaches. The analysis technique used is multiple regression and hypothesis testing using partial t-test and F test simultaneously with a significance level of 5%. The results showed that Return on Assets had a negative and significant effect on stock returns with a significance value of 0,000 and had a t-value of -4.176 (greater than t table-1.98447). Price to Book Value has a positive and significant effect on stock returns with a significance value of 0.010 and a t value of 2.623. All independent variables simultaneously proved to have a significant effect on stock returns with a significance value of 0.001.